Corporate agility and monetary policy transmission - Colak, Gonul; Mai, Sinh Thoi (Journal of Corporate Finance, 2026)
Corporate agility – the ability to respond quickly and effectively to changing business conditions – is crucial for firms' success. While important, this concept is difficult to measure and use in quantitative research. By applying machine learning techniques, we develop reliable measures of agility and analyse how agile firms manage exposure to monetary policy uncertainty, a significant and frequently occurring form of threat. Agile firms' stocks are significantly less exposed to this uncertainty as they proactively apply risk management techniques to reduce their exposure. This has real consequences: agile firms' investments are less affected by monetary policy tightening episodes.